ENHANCING DISASTER RESILIENCE INDICATORS TOWARDS APPROPRIATED MITIGATING STRATEGIES: SYSTEMATIC LITERATURE REVIEW APPROACH - Istiqomah, Asti; Fauzi, Akhmad; Mulatsih, Sri; Nuva, Nuva; Wijayanti, Pini (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2026)
Developing a regional resilience index for natural disasters is essential for systematically monitoring resilience performance and supporting evidence-based policymaking. Strengthening regional resilience is particularly critical for West Java Province, given its high exposure and vulnerability to multiple hazards. This study aims to construct a comprehensive framework of regional disaster resilience indicators and to assess the level of resilience across the province. The research employs a Systematic Literature Review (SLR) and the PROMETHEE (Preference Ranking Organization Method for Enrichment Evaluation) for multi-criteria analysis. Secondary data were obtained from Statistics of West Java Province, while the SLR was conducted using the Scopus database complemented by manual searches. A total of 77 selected articles yielded 22 principal indicators of regional disaster resilience, classified into five dimensions: economic, social, ecological, infrastructure, and institutional. The assessment reveals that several indicators—particularly within the ecological, infrastructure, and institutional dimensions—demonstrate relatively low performance across districts and cities. Based on 17 equally weighted indicators, the ranking results identify Cimahi City, Bandung City, and Cirebon City as the three most resilient regions in the province. Meanwhile, Tasikmalaya City, Cianjur City, and Indramayu City ranked lowest in terms of disaster resilience. These findings provide an empirical basis for stakeholders and policymakers to evaluate regional resilience capacity and formulate integrated action plans and targeted mitigation strategies to support sustainable and adaptive regional development.